Strategi Penanganan Pembiayaan Bermasalah di BWM Syubbanul Wathon Maslahah - Indahsari, Sutriyana; Fitriyani, Yeny; Purwanto, Purwanto (Forum Kerjasama Pendidikan Tinggi, 2024)
Handling problematic financing is an important aspect of maintaining the stability and sustainability of Sharia microfinance institutions. This research was conducted to analyze the strategy for managing complex funding implemented by the Syubbanul Wathon Maslahah Micro Waqf Bank. This type of qualitative research was used in this research. Research data was collected through in-depth interviews, observation and documentation. Data analysis was carried out using an interactive model, which involved data reduction activities, data presentation, and conclusion. The research results present information that reveals two approaches adopted by the Syubbanul Wathon Maslahah Micro Waqf Bank in dealing with financing problems. In situations where the death of a customer causes financing problems, the bank applies policies that are consistent with the careful aa principle. In this case, the customer's remaining arrears are considered paid, meaning that the benevolent loan can be considered fulfilled. This approach reflects the bank's commitment to ethical and human values, where financial policies are not only believed in terms of formalities but also pay attention to social and humanitarian aspects. On the other hand, when financing problems are caused by the customer's inability to repay the financing, Syubbanul Wathon Maslahah Micro Waqf Bank implements a series of strategies. A personal approach is prioritized, with the bank seeking to understand in depth the causes of customer incompetence.